2017
DOI: 10.1002/em.22127
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity, telomere length and hTERT DNA methylation in peripheral blood mononuclear cells from monozygotic twins with discordant smoking habits

Abstract: Increased telomerase expression has been implicated in the pathogenesis of lung cancer and, since the primary cause of lung cancer is smoking, an association between telomerase reactivation and tobacco smoke has been proposed. In this work an investigation has been performed to assess the relationship between tobacco smoke exposure and telomerase activity (TA) in peripheral blood mononuclear cells of healthy smokers. The methylation status of the catalytic subunit of telomerase hTERT was concurrently investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…However, this is unlikely since BMI was not an independent predictor of TL in our regression analysis in HC or AUD participants. Similarly, while exposure to tobacco has been associated with TL (Marcon et al 2017) in our sample, Fagerstrom score was associated with AUD, but with TL only at a trend level (p < 0.1). Because we do not have data for past exposure to tobacco, we cannot rule out the possibility that the combination of heavy drinking and past smoke exposure might have contributed to shorter telomeres in AUD.…”
Section: Discussionsupporting
confidence: 43%
“…However, this is unlikely since BMI was not an independent predictor of TL in our regression analysis in HC or AUD participants. Similarly, while exposure to tobacco has been associated with TL (Marcon et al 2017) in our sample, Fagerstrom score was associated with AUD, but with TL only at a trend level (p < 0.1). Because we do not have data for past exposure to tobacco, we cannot rule out the possibility that the combination of heavy drinking and past smoke exposure might have contributed to shorter telomeres in AUD.…”
Section: Discussionsupporting
confidence: 43%
“…A similar effect is observed in psychological stress in terms of OxS and TL, also showing lower telomerase activity [309]. Regarding smoking, there are contradictory results over the TL [310]; however, most studies suggest that there is a shortening of telomeres in smokers [311] associated with lipoperoxidation [312]. In addition, the consumption of sugary carbonated beverages is associated with shorter telomeres [313], even if the consumption starts from the early stages of life and before the development of obesity [314].…”
Section: Effect Of Healthy Lifestyles On Oxidative Stress and The Telomere Lengthmentioning
confidence: 76%
“…Of the 83 articles reviewed, 27 analyzed cigarette smoking and TL, all of which were observational studies (ethical reasons are crucial here explaining the lack of intervention studies). We grouped these observational studies in cross-sectional ( Table 4 ) [ 60 , 67 , 77 , 93 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ] and in case-control and longitudinal studies ( Table 5 ) [ 121 , 122 , 123 , 124 , 125 , 126 , 127 ]. There were 20 cross-sectional studies [ 60 , 67 , 77 , 93 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ], 2 case-control studies [ 124 , 127 ], and 5 longitudinal studies [ 121 , …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, contradictory findings were reported in a methylation and gene expression study carried out on twins. The authors observed greater telomerase activity and greater TL in smokers than in non-smokers [ 124 ].…”
Section: Resultsmentioning
confidence: 99%